Utilização de nitrato de amônio e de uréia como fontes de nitrogênio na micropropagação de amoreira-preta - Villa, Fabíola; Pasqual, Moacir; Pio, Leila Aparecida Salles; Fráguas, Chrystiane Borges [UNESP]; De Rezende, Juliana Costa (My University, 2009)
The high cost allied to the difficulty in the acquisition of the ammonium nitrate has been taking the accomplishment of works looking for an alternative for the substitution of this source of nitrogen. It was aimed at to study the technical viability of the substitution of the ammonium nitrate for urea, as source of nitrogen in the culture media for the blackberry in vitro cv. Tupy (Rubus sp). Nodal segments were used, already established in vitro, were inoculated in culture media MS and 50% MS, added of 1.0 mg. dm-3 of BAP, solidified with 6 g.dm-3 of agar, pH was adjusted for 5,8 and sterilized to 121 °C and 0,1 MPa for 20 min. The treatments consisted of the substitution of 0; 20; 40; 60; 80 and 100% of NH4NO3 for urea, and the swinging of nitrogen supplied by the culture media MS it was not altered. The explants were maintained by 60 days in growth room with temperature of 27±1 °C, photoperiod of 16 h and luminous intensity of 32 mmol m'2 s'1. The experiment was arranged in a completely randomized design, in factorial (6 x 2) using four repetitions with 16 plants each one. From the obtained results it can be concluded that the urea doesn't substitute NH 4NO3 in the culture media MS as nitrogen source in the culture vitro of blackberry.
Utilization of amonium nitrate and urea as nitrogen sources in the blackberry micropropagation
Keywords: Culture media MS; Nitrogen; Rubus sp.